A review of the family Alycidae (Acari, Acariformes) from South Africa - Uusitalo, Matti; Ueckermann, Edward A.; Theron, Pieter D. (Zootaxa, 2020)
A taxonomic study of the family Alycidae G. Canestrini & Fanzago in South Africa revealed nine species of which seven are new to science: Alycus augrabiensis sp. nov., Pachygnathus nasutus sp. nov., Amphialycus acaciae sp. nov., A. adustus sp. nov., A. mayteni sp. nov. (Alycini); Laminamichaelia furcula sp. nov. (Bimichaeliini); and Proteromichaelia sila gen. et sp. nov. (Proteromichaeliini trib. nov.). The four previously known species of Alycidae are redescribed: Amphialycus oblongus (Halbert, 1920), Laminamichaelia shibai nom. nov. (=B. ramosus Shiba, 1976, nom. preocc.), Petralycus longicornis Theron, 1977 and P. brevicornis Theron, 1977. Keys to tribes of the family Alycidae and to genera and species recorded in South Africa are provided.